Miyazakiworld a life in art - Napier, Susan (New Haven Yale University Press, 2018)
The story of filmmaker Hayao Miyazaki's life and work, including his significant impact on Japan and the world—'an essential work in anime scholarship.” (Angelica Frey, Hyperallergic) A thirtieth†‘century toxic jungle, a bathhouse for tired gods, a red†‘haired fish girl, and a furry woodland spirit—what do these have in common?

They all spring from the mind of Hayao Miyazaki, one of the greatest living animators, known worldwide for films such as My Neighbor Totoro, Princess Mononoke, Spirited Away, Howl's Moving Castle, and The Wind Rises.

Japanese culture and animation scholar Susan Napier explores the life and art of this extraordinary Japanese filmmaker to provide a definitive account of his oeuvre. Napier insightfully illuminates the multiple themes crisscrossing his work, from empowered women to environmental nightmares to utopian dreams, creating an unforgettable portrait of a man whose art challenged Hollywood dominance and ushered in a new chapter of global popular culture.
Keywords: Miyazaki, Hayao, 1941-.; Animators -- Japan -- Biography; Animated films -- Japan